2012
DOI: 10.1101/gad.182014.111
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of linker histone H1.4 Lys 34 acetylation in transcriptional activation

Abstract: The linker histone H1 is a key player in chromatin organization, yet our understanding of the regulation of H1 functions by post-translational modifications is very limited. We provide here the first functional characterization of H1 acetylation. We show that H1.4K34 acetylation (H1.4K34ac) is mediated by GCN5 and is preferentially enriched at promoters of active genes, where it stimulates transcription by increasing H1 mobility and recruiting a general transcription factor. H1.4K34ac is dynamic during spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 38 publications
1
72
0
Order By: Relevance
“…Despite the fact that linker histone subtypes act as redundant proteins in knock-out mice (30,33), new data show that each tissue is characterized by a specific set of expressed linker histone subtypes (27,52,53). The globular central domain of the linker histone is highly conserved among the subtypes, but the N-and C-terminal domains are divergent with the C-terminal domain showing especially strong variations in its length and charge.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that linker histone subtypes act as redundant proteins in knock-out mice (30,33), new data show that each tissue is characterized by a specific set of expressed linker histone subtypes (27,52,53). The globular central domain of the linker histone is highly conserved among the subtypes, but the N-and C-terminal domains are divergent with the C-terminal domain showing especially strong variations in its length and charge.…”
Section: Discussionmentioning
confidence: 99%
“…Is this a relevant in vivo activity? Future studies will address this, but it is worth mentioning that a recent study showed that human Gcn5 acetylates H1.4 at K34ac during transcription activation (63). Keeping in mind its evolutionary relationship with Rtt109, it will be interesting to determine whether p300/CBP also acetylates linker histone.…”
Section: Discussionmentioning
confidence: 99%
“…recently beginning to be appreciated. Of particular note is acetylation of a conserved lysine at position 34 on histone H1.4 (H1.4K34Ac), which is associated with increased H1 mobility and transcriptional activation (26). Compared with the core histones, which remain in place for several hours, H1 proteins are substantially more mobile with a mean residence time at any one binding site estimated to be ϳ3 min (43), albeit less mobile than transcription factors that boast mean residence times of 5-25 s (44).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that Lys-34 in histone H1.2/1.3-the peptide KASGPPVSELITK being common to both histone variants-is also subject to acetylation, monomethylation, and formylation (25). Interestingly, the same lysine residue is also acetylated in histone variant H1.4 (H1.4K34Ac), a modification recently shown to be associated with transcriptional activation (26).…”
Section: Cps1 Is Required For Nuclear Proteinmentioning
confidence: 99%